Penerapan Model Direct Intruction Dalam Meningkatkan Kemampuan Membaca Dan Menghafal Q.S At-Tiin Pada Siswa Kelas IV Sdn 19 Tanjung Durian - Wulan Dari, Uci (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to determine the effect of implementing the Direct Instruction teaching model in improving students' learning outcomes in Islamic Education (PAI) at SDN 19 Tanjung Durian, focusing on the topics of Q.S At-Tiin and Asmaul Husna. The research used a classroom action research approach, carried out in two cycles. The results show that in Cycle I, 50% of students achieved the learning completion with a KKTP score of 70, while in Cycle II, 83.33% of students reached classical completion. This improvement was achieved through enhanced lesson planning, the use of IT-based media, and more intensive group discussions. Therefore, it can be concluded that the Direct Instruction model, combined with technology and group work, can improve students' learning outcomes.